The Eleventh Marcel Grossmann Meeting 2008
DOI: 10.1142/9789812834300_0339
|View full text |Cite
|
Sign up to set email alerts
|

Optical Reference Geometry and Inertial Forces in Kerr-De Sitter Spacetimes

Abstract: Abstract. Optical reference geometry and related concept of inertial forces are investigated in Kerr-de Sitter spacetimes. Properties of the inertial forces are summarized and their typical behaviour is illustrated. The intuitive 'Newtonian' application of the forces in the relativistic dynamics is demonstrated in the case of the test particle circular motion, static equilibrium positions and perfect fluid toroidal configurations. Features of the optical geometry are illustrated by the embedding diagrams of it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…The velocity profiles of the geodetical discs and perfect fluid tori in the locally non-rotating frames were studied in [37,38,39,40,41,42]. Further, the test particle and perfect fluid properties were treated also in the framework of the optical reference geometry [43,44,45] allowing introduction of inertial forces in the intuitive Newtonian way [46]. Motion of photons in the Reissner-Nordström-de Sitter and more general Kerr-Newman-(anti-)de Sitter spacetimes is discussed in the papers [47,48].…”
Section: Introductionmentioning
confidence: 99%
“…The velocity profiles of the geodetical discs and perfect fluid tori in the locally non-rotating frames were studied in [37,38,39,40,41,42]. Further, the test particle and perfect fluid properties were treated also in the framework of the optical reference geometry [43,44,45] allowing introduction of inertial forces in the intuitive Newtonian way [46]. Motion of photons in the Reissner-Nordström-de Sitter and more general Kerr-Newman-(anti-)de Sitter spacetimes is discussed in the papers [47,48].…”
Section: Introductionmentioning
confidence: 99%
“…Even if the results presented in Subsec. 4.1 are mostly known from mapping of the test particle motion in conformal hypersurfaces [36,44,45,48,50], they enclose and contextualize the brand-new results introduced in Subsec. 4.2.…”
Section: Introductionmentioning
confidence: 93%
“…in the case of a general motion, as it follows from relations (21) and (55) [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50]. Thus, the fluid flow lines in Σ t along which the centrifugal force vanishes independently of velocity are mapped by geodesics inΣ t .…”
Section: Conformal Transformation C = E −φmentioning
confidence: 99%
See 1 more Smart Citation
“…By the use of embedding diagrams of both ordinary geometry and optical reference geometry, Refs. [20] and [21] have shown that in the vicinity of the static radius, the geometry of de Sitter space-time is analogous to an asymptotically flat space-time. Thus, eq.…”
Section: Introductionmentioning
confidence: 99%